Persistent zinc-ion storage in mass-produced V2O5 architectures. (June 2019) - Chen, Dong; Rui, Xianhong; Zhang, Qi; Geng, Hongbo; Gan, Liyong; Zhang, Wei; Li, Chengchao; Huang, Shaoming; Yu, Yan
Abstract: Rechargeable zinc-ion batteries (ZIBs) appear to be a promising candidate for large-scale energy storage system because of the abundance and inherent safety of the zinc negative electrode. Despite these benefits, huge polarization caused by the intercalation of multivalent charge carrier Zn 2+ into the cathodic hosts remains a long-standing challenge impeding the development of high-performance ZIBs. Herein, we demonstrate the viability of the V2 O5 nanorods constructed 3D porous architectures (3D-NRAs-V2 O5 ) as cathode for ZIBs. Notably, the 3D-NRAs-V2 O5 can be scaled up to kilo-gram production based on a simple sol-gel reaction followed by an annealing process. The synergic contributions from the 3D porous framework and layered structures of the 3D-NRAs-V2 O5 lead a more facile Zn 2+ ions (de)intercalation storage process. Consequently, it offers high reversible capacity of 336 mAh g −1 at a high current density of 50 mA g −1 and exhibits excellent long-term cyclic stability with a capacity retention of 85% over 5000 cycles at a high current density of 10 A g −1 . Furthermore, the use of various ex-situ characterization techniques and first-principles calculations has successfully unravelled the Zn 2+ ions storage mechanism of the 3D-NRAs-V2 O5. Besides the excellent electrochemical performance of the 3D-NRAs-V2 O5, it can also be easily scaled up based on the simple synthetic protocol, which shows great potential to be practically used for the next-generation large-scale energy storage applications. Graphical abstract: Image 1 Highlights: Nanorods-constructed 3D porous V2 O5 architectures (3D-NRAs-V2 O5 ) are fabricated. The production of 3D-NRAs-V2 O5 is kilo-scale (1.185 kg). 3D-NRAs-V2 O5 cathode offers Zn-ion storage capacity of 336 mAh g −1 at 50 mA g −1 . Long-term cyclic stability (5000 cycles) at 10 A g −1 is displayed. The zinc storage mechanisms are revealed by a post-mortem analysis.